A novel combined animal tissue model for freehand and ultrasound‐guided fine needle aspiration biopsy and smear preparation techniques training. Issue 1 (21st August 2020) - Kebe Radulović, Maja; Vivoda Tomšič, Martina; Cimerman, Damjana; Gutnik, Helena; Strojan Fležar, Margareta
Abstract: Objective: A variety of models are used for fine needle aspiration biopsy (FNAB) and smear preparation techniques training: human, animal and silicon models or combined models. We present fresh animal tissues as models for freehand and ultrasound (US)‐guided FNAB technique training, enabling an integrated approach from tumour detection to smear evaluation. Methods: We introduced a novel combined animal tissue model using dietary animal meat with covering skin as a substrate. Animal liver tissue of various sizes, representing tumour, was inserted into the various layers of the substrate (subcutaneous fat, muscle tissue, proximity of bone). Freehand and US‐guided FNAB smear preparation, including fixation, was then performed and assessed. Results: The use of a combined animal tissue model for 6 freehand and 3 US‐guided FNAB sessions showed a statistically significant improvement in the US‐guided FNAB retrieval of liver tissue (Fisher's exact test, p = .0216), in smear preparation technique reflected in a decrease in the number of too thick smears after freehand FNAB (Fisher's exact test, p = .0070), in the overall number of smears satisfactory for evaluation by US‐guided FNAB (Fisher's exact test, p = .0206) and in the number of flawless smears obtained in the freehand FNAB training sessions (Fisher's exact test, p = .0020). Conclusions: A unique advantage of the presented model encompassing various layers of animal tissues with covering skin, offers an integrated approach for FNAB training from "tumour" detection, puncture precision, to smear preparation and cytological evaluation for a wider audience and does not compromise patient safety.